COLLABORATIVE SUPERVISION STRATEGY INTEGRATED WITH SISPENA APPLICATION FOR IMPROVING EARLY CHILDHOOD INSTITUTION’S ACCREDITATION (THUFULA, 2023)
The research purpose is to provide insights into how the collaborative supervision strategy, supported by the SISPENA application, addresses accreditation challenges and promotes educational excellence in TAAM institutions. The research used qualitative approach with case study method. Data were gathered using  in-depth interviews with educators, supervisors, and administrators from participating TAAM institutions, participant observation, and document study. The data were analyzed using triangulation to gain insights into the challenges faced in meeting accreditation criteria and the collaborative supervision strategy's impact on addressing these challenges. The findings highlight the challenges arising from limited resources and inconsistencies in accreditation readiness. The collaborative supervision strategy was then introduced to facilitate collective discussions among educators, supervisors, and administrators. The integration of the SISPENA application played a vital role, offering technological support and a platform for streamlined documentation. The research underscores the roles of each stakeholder group: educators engage in discussions and implement improved teaching methods, supervisors guide discussions and oversee documentation, and administrators manage the documentation process. The collaborative strategy's effectiveness is evidenced by the tangible progress observed in accreditation processes across the seven participating TAAM institutions.